Biosynthesis of gold nanoparticles in the fruiting body of enoki mushrooms (Flammulina velutipes) under Pb2+ induction. Issue 2 (19th November 2022) - Mo, Jingang; Jin, Jun; Yu, Han; Ai, Mingjun; Hu, Die; Li, Linlin; Song, Kai
Abstract: Fungi can produce many compounds, such as proteins, enzymes, amino acids, and polysaccharides, which are internalised and enriched for metals, and are widely used as reducing and stabilising agents for the biosynthesis of gold nanoparticles (Au NPs). Almost all fungal sources used in the synthesis of the Au NPs are in the form of cell filtrates or mycelial suspensions. However, the culture of cell‐free fungal filtrate and mycelium is not comparable to the propagation of fungal substrates in input and operation. Here, we evaluated in vivo biosynthesis of Au NPs in enoki mushrooms ( Flammulina velutipes ). HAuCl4 was reduced in the fruiting body of the enoki mushrooms via induction by Pb 2+, resulting in the generation of Au NPs. We then employed UV‐Vis absorption spectroscopy, Transmission Electron Microscope, and Energy Dispersive Spectrometer to characterise various shapes of the Au NPs. The elemental analysis indicated that the Au NPs were mainly concentrated in organelles of the stalk and cap cells. We also demonstrated that 0.3–0.5 mM HAuCl4 was the optimal stress treatment concentration based on the changes in physiological indicators of the enoki mushrooms. This work reveals that fungi can be utilised well as nanomaterial bioreactors. Abstract : HAuCl4 was reduced by fruiting body of the enoki mushrooms via induction by Pb2+, which resulted in production of Au NPs.